156k views
2 votes
How do I solve 6(5 - 2x) + 12 = -66?

User HerrKaputt
by
5.5k points

2 Answers

5 votes

Answer:x = 9/12

Explanation:

User Marius Tanasoiu
by
6.4k points
6 votes

Answer:

x = 9

Explanation:

Step 1: Write equation

6(5 - 2x) + 12 = -66

Step 2: Solve for x

  1. Distribute 6: 30 - 12x + 12 = -66
  2. Combine like terms: 42 - 12x = -66
  3. Subtract 42 on both sides: -12x = -108
  4. Divide both sides by -12: x = 9

Step 3: Check

Plug in x to verify it's a solution.

6(5 - 2(9)) + 12 = -66

6(5 - 18) + 12 = -66

6(-13) + 12 = -66

-78 + 12 = -66

-66 = -66

User Friendly Crook
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.